Peran Santri dalam Menjaga Kebersihan Lingkungan Hidup di Pondok Pesantren Annuqayah Latee I Pada Masa Pandemi - Rozinah AS; Halimatus Sa'diyah (Jurnal Penelitian, 2021)
This study aims to answer questions regarding the implementation of clean attitudes in the pesantren tradition related to the clean lifestyle of students in their daily behavior, which leads to a hedonic attitude. This hedonistic attitude refers to how much the students care about the pesantren environment they live in. The method used in this research is a descriptive qualitative approach. Data collection instruments were obtained by means of field observations, in-depth interviews with several informants as data complements, and documentation. The results of this study indicate that the phenomenological study that the researcher uses as a tool to understand the attitudes of students towards cleanliness is functioning well. The implication is that in this phenomenological study, the development of civilization shows the increasingly sad attitude of the students to care about their environment, both the general environment and the individual students (body hygiene). The transcript of the interview results was coded and then poured into synthesis and interpretation, this adjusted to the condition of the pesantren, the existing situation, the facilities and habits of the students in relation to life in maintaining the cleanliness of the dormitory environment. All of this is good because of the laziness that is brought from the environment of students before boarding (home), as well as from the environment they are facing at the Islamic boarding school, such as the influence of friends, the lack of education of students in managing time in the midst of dense boarding school activities and so on.